Explorations in environmental and natural resource economics essays in honor of Gardner M. Brown, Jr. - Brown, Gardner Mallard; Halvorsen, Robert; Layton, David, F., 1967-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar Pub., 2006)
Gardner M. Brown, Jr. has been a leading innovator in the development of environmental and natural resource economics. This book comprises essays written in his honor by some of the most distinguished economists working in this field.
pt. 1. Conservation of biological resources -- pt. 2. Resource modeling, growth and environmental quality -- pt. 3. Theory and practice of valuation.
Includes bibliographical references and index.
Keywords: Environmental economics; Economic development -- Environmental aspects; Natural resources -- Management; Electronic books